Backpropagation neural networks modelling of photocatalytic degradation of organic pollutants using TiO2-based photocatalysts - Ayodele B.V.; Alsaffar M.A.; Mustapa S.I.; Vo D.-V.N. (John Wiley and Sons Ltd, 2023)
Backpropagation; Catalysts; Chemical industry; Degradation; Ketones; Network architecture; Neural networks; Photocatalysts; Polycyclic aromatic hydrocarbons; Silver compounds; Titanium dioxide; Titanium oxides; Advanced Oxidation Processes; Back propagation artificial neural network (BPANN); Back propagation neural networks; Methyl blue degradation; Non-linear relationships; Optimized architectures; Photo catalytic degradation; TiO2-based photocatalysts; Organic pollutants; anthraquinone; dye; ferrous gluconate; indole; silver; titanium dioxide; Article; back propagation neural network; chemical oxygen demand; flow rate; leaching; photocatalysis; photodegradation; pollutant; reaction duration (chemistry); ultraviolet radiation; waste water management